Participatory strategies for implementing sustainable agrifood systems in the Amazon - Maya, Diana; Guaquetá, Victoria; Correal, Antonia; Vanegas Cubillos, Martha (2024)
Exchange of experiences is a powerful pedagogical strategy for capacity building by enabling knowledge sharing. It recognizes the value of local knowledge in dialogue with academic knowledge for the co-creation of sociotechnical innovations. Through the exchange of experiences, participants gain new perspectives, develop social skills, feel empowered to achieve their goals, and build relationships with others. Horizontal communication, interaction, trust and reflection are essential characteristics that ensure that the exchange of experiences is enriching and beneficial for all involved.